Kemampuan Penyerapan Tenaga Kerja, Pendidikan Dan Kesehatan Dalam Menjelaskan Variasi Pertumbuhan Ekonomi Kabupaten/Kota Di Provinsi Kalimantan Barat - B01112090, zarina (Jurnal Curvanomic, 2017)
Absorption Ability Of Labor, Health Education And Economic Growth In Explaining The Variation Of District / City In The Province Of West Kalimantan